2015
DOI: 10.1017/s1755267214001432
|View full text |Cite
|
Sign up to set email alerts
|

New records of whale shark (Rhincodon typus), giant manta ray (Manta birostris) and Chilean devil ray (Mobula tarapacana) for Suriname

Abstract: Little is known about elasmobranchs along the northern coast of South America. During five boat surveys in Suriname offshore waters we visually documented the presence and behaviour of the free-ranging whale shark Rhincodon typus and two mobulid rays: the giant manta ray Manta birostris and the Chilean devil ray Mobula tarapacana. Three sightings were made of R. typus at the surface in shallow coastal waters where the water depth measured 46-67 m. One of these sightings was confirmed by photographs. Manta biro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Identifying the taxon of Mobula to species can be problematic because of the similarities between some Mobula species (Couturier et al, 2012;De Boer et al, 2015). This is particularly true for the smaller species of Mobula such as M. hypostoma.…”
mentioning
confidence: 99%
“…Identifying the taxon of Mobula to species can be problematic because of the similarities between some Mobula species (Couturier et al, 2012;De Boer et al, 2015). This is particularly true for the smaller species of Mobula such as M. hypostoma.…”
mentioning
confidence: 99%
“…However, Yano et al (1999) reported that mantas can swim at 2.78-4.17 m s −1 when males are chasing females during mating. In addition, mantas perform aerial leaps clearing the water (Coles, 1916;Rayner, 1986;Homma et al, 1997;Duffy and Abbott, 2003;De Boer et al, 2015). The physics of such leaps requires high-speed swimming (Rohr et al, 2002).…”
Section: Manta Turning Performancementioning
confidence: 99%
“…Including the putative manta ray species (Hinojosa-Alvarez et al, 2016), six mobulid species are reported for the western Atlantic Ocean: The oceanic manta ray, Mobula birostris (Walbaum, 1792) Menni & Stehmann, 2000;Milessi & Oddone, 2003;Mendonça et al, 2012;De Boer et al, 2015;Del Moral-Flores et al, 2015;Last et al, 2016;Ehemann et al, 2018Ehemann et al, , 2019Stevens et al, 2018;Mejía-Falla & Navia, 2019;Pate & Marshall, 2020;Trujillo-Cordova et al, 2020), the Caribbean manta ray, M. cf. birostris (Walbaum, 1792) (Bucair, Venables, et al, 2021;Hinojosa-Alvarez et al, 2016;Pate & Marshall, 2020;Stevens et al, 2018), the Atlantic pygmy devil ray, Mobula hypostoma (Bancroft, 1831) (Campbell & Munroe, 1974;Cousseau & Menni, 1983;Del Moral-Flores et al, 2015Ehemann et al, 2018Ehemann et al, , 2019Jones et al, 2020;Last et al, 2016;Menni & Stehmann, 2000;Stevens et al, 2018), the spinetail devil ray Mobula mobular (Bonnaterre, 1788), Del Moral-Flores et al, 2015;Mas et al, 2015;Last et al, 2016;Ehemann et al, 2018;Stevens et al, 2018;Hauser-Davis et al, 2021), the sicklefin devil ray Mobula tarapacana (Philippi, 1892) (Childs, 1997;De Boer et al, 2015;Del Moral-Flores et al, 2015;Ehemann et al, 2018;…”
Section: Introductionmentioning
confidence: 99%
“…Including the putative manta ray species (Hinojosa‐Alvarez et al ., 2016), six mobulid species are reported for the western Atlantic Ocean: The oceanic manta ray, Mobula birostris (Walbaum, 1792) Menni & Stehmann, 2000; Milessi & Oddone, 2003; Mendonça et al ., 2012; De Boer et al ., 2015; Del Moral‐Flores et al ., 2015; Last et al ., 2016; Ehemann et al ., 2018, 2019; Stevens et al ., 2018; Mejía‐Falla & Navia, 2019; Pate & Marshall, 2020; Trujillo‐Cordova et al ., 2020), the Caribbean manta ray, M . cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation